2018
DOI: 10.5547/2160-5890.7.2.jclu
|View full text |Cite
|
Sign up to set email alerts
|

Winners and Losers of EU Emissions Trading: Insights from the EUTL Transfer Dataset

Abstract: This paper analyzes distributional effects the EU Emissions Trading Scheme (EU ETS) created between participants of the scheme during its first trading period. To this end, a dataset recording all transfers during the first period of the EU ETS, originally at account level, was enhanced by adding information about parent companies, firm characteristics, and carbon prices. A two-step selection model was formulated and applied to the data.To account for a number of uncertainties, sensitivity analysis with regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Since there had been few previous attempts to collect installation‐level CO 2 emissions data, too, there were substantial informational asymmetries between national regulators and polluters. Many NAPs were consequently produced on the basis of very little information and were subject to intense rent‐seeking and lobbying, especially from the largest firms and trade associations in the most polluting sectors (Cludius, 2018; Hanoteau, 2014; Thomas, 2021). Perversely, the fact that NAPs were based on historical baseline emissions that were to be updated over time also introduced a theoretical “moral hazard,” where plants might be incentivized to emit more in the short‐term in the expectation of getting more free allowances in the future (Grubb & Neuhoff, 2006).…”
Section: Evolution Of the Eu Etsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there had been few previous attempts to collect installation‐level CO 2 emissions data, too, there were substantial informational asymmetries between national regulators and polluters. Many NAPs were consequently produced on the basis of very little information and were subject to intense rent‐seeking and lobbying, especially from the largest firms and trade associations in the most polluting sectors (Cludius, 2018; Hanoteau, 2014; Thomas, 2021). Perversely, the fact that NAPs were based on historical baseline emissions that were to be updated over time also introduced a theoretical “moral hazard,” where plants might be incentivized to emit more in the short‐term in the expectation of getting more free allowances in the future (Grubb & Neuhoff, 2006).…”
Section: Evolution Of the Eu Etsmentioning
confidence: 99%
“…Politically, the rents that accrued to industry through free allocation not only led some industries to support rather than oppose the ETS, but also created a lobby to preserve those rents (Fuchs & Feldhoff, 2016). Meanwhile, the fact that some of the biggest polluters ended up profiting the most (Cludius, 2018) also sowed the seeds for public outcry and reform (Paterson, 2013). Economically, focus shifted from the static cost‐effectiveness of emissions trading towards the effects that allocation rules could have in a dynamic setting.…”
Section: Introductionmentioning
confidence: 99%
“…As explained above, in the first two phases the EU member states were responsible for developing NAPs, which had to be approved by the EU Commission (Bailey and Maresh, 2009). Cludius (2018) and Morris (2012) assessed which companies had the largest surplus of free allocation in Phase 1 and Phase 2, respectively. Both studies show that it was especially companies in the steel and cement sectors that had excess allocations and that the level of excess allocation was a major determinant for which companies would become potential "winners" or "losers."…”
Section: Lobbying Effort and Rent Seeking In The Eu Etsmentioning
confidence: 99%
“…We drew on the information provided by the European University Institute (EUI) (Jaraite et al, 2013) that links individual accounts to companies using the ORBIS database. We also relied on previous work for aggregating further accounts based on company structures of the first trading period (Betz and Schmidt, 2015;Cludius, 2018). This enabled us to link all active accounts in the first dataset (12,219) to their parent companies (5,216).…”
Section: The Eutl Datasetmentioning
confidence: 99%
“…He determined that active trading of EU allowances is driven by the size (measured by turnover) of a company, its sector and ownership structure, as well as the level of free allocation. Cludius (2018) investigated the drivers for gains and losses made on the EU emissions market and found that the level of excess allocation as well as the choice of when to enter the market are important in driving gains and losses of regulated companies. She also discovered that large companies (both in terms of their emissions and the number of accounts held) and companies short on trading allowances were more likely to become active during the first period of EU emissions trading.…”
Section: Introductionmentioning
confidence: 99%